TENUN SONGKET TANJUNG PINANG KAJIAN SEMIOTIK Fenomenalogi: Identitas Sosial Masyarakat kampung Tanjung Pinang - Arsan Shanie (Universitas Trisakti, 2020)
AbstractSemiotics is the study of signs of meaning. Everything that can be observed or observedsees a work of art more fully so that it can inform a value contained therein anddescribe a cultural context. Semiotics in the Meaning of an object is not only limited tothe form that is seen visually, but is expected to be able to interpret the essential thingsveiled in a form that can be identified through in-depth observation.Traditional Songket is a woven fabric made by the technique of adding weft asa decoration by inserting silver, gold or colored threads above the warp. The word“Songket” is derived from the words “Puncture” and “Cukit” which is synchronized to“Sukit” then changes to “Sungki”, and finally becomes “Songket” Weaving Songket.Tanjung Pinang is one of the oldest songket artisans in South Sumatra, traditionalsongket cloth in Tanjung Pinang village, Ogan ilir Regency is a type of cloth used asa symbol of honor for the people of Tanjung Pinang Village. The cloth is used duringcertain traditional activities, such as South Sumatra traditional traditional clothing,wedding ceremonies, marhaba (inauguration of the child’s name and shaving orwelcome). The traditional songket of Tanjung Pinang village, Ogan ilir Regency isone of the cultural heritages as a form of social identity. This is illustrated in theembodiment of forms, motifs and decoration in which the physical form of traditionalfabrics depicts aesthetic elements and is bound by cultural values prevailingin society.The form and manifestation can be studied in more depth. AbstrakSemiotika merupakan ilmu yang mempelajari tentang tanda pemaknaannya.Segala sesuatu yang dapat diamati atau teramati melihat sebuah karya senisecara lebih utuh sehingga dapat menginformasikan suatu nilai yang terdapat didalamnya serta mendeskripsikan suatu konteks budaya. Semiotika dalam .Pemaknaan sebuah objek tidak hanya terbatas pada bentuk yang dilihat secaravisual, tetapi diharapkan mampu mengartikan hal yang esensial terselubungdalam bentuk yang dapat diidentifikasi melalui pengamatan yang mendalam.Songket Tradisional adalah kain tenun yang dibuat dengan teknik menambahkan benang pakan sebagai hiasan dengan menyisipkan benang perak, emas atau benang warna di atas lungsin. Kata “ Songket “ berasal dari kata “Tusuk“ dan “Cukit“ yang diakronimkan menjadi “Sukit” kemudian berubah menjadi “Sungki”, dan akhirnya menjadi “ Songket” Tenun songket. Tanjung Pinang merupakan salah satu daerah pengrajin songket tertua diSumatra Selatan, Kain songket tradisional desa Tanjung Pinang KabupatenOgan ilir adalah jenis kain yang dipakai sebagai simbol kehormatanmasyarakat Desa tanjung pinang, Kain tersebut digunakan pada saat kegiatan tradisi tertentu, seperti busana tradisional adat Sumatera Selatan, upacara pernikahan, marhaba (peresmian nama dan pencukuran anak atau ucapan selamat datang). Kain songket tradisional desa Tanjung Pinang Kabupaten Ogan ilir adalah salah satu warisan budaya masyarakat sebagai wujud dari identitas sosial. Hal ini tergambar dalam perwujudan bentuk, motif dan ragam hias dimana dalam bentuk fisik kain tradisional yang menggambarkan unsur keindahan (estetika) dan terikat oleh nilai-nilai budaya yang berlaku dalam masyarakat. Bentuk dan perwujudannya dapat dikaji secara lebih mendalam.